EFEKTIFITAS METODE DISKUSI KELOMPOK DAN METODE CERAMAH TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP REMAJA TENTANG PERILAKU SEKS PRANIKAH (Study Kasus Remaja Kelas X IPA Di Sma Negeri 01 Bengkayang) - Ardila, Aris; Ridha, Abduh; Jauhari, Abdul Haris (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2014)
The enhancement of premarital sexual behavior among adolescents resulting in adverse effects. Therefore, preventive measures to this behavior need to be done. Lecture and discussion methods can be conducted to increase the adolescents’ knowledge and behavior as these methods provide them with the information about the causes and effect, as well as the prevention of the premarital sexual behavior.This study aimed at discovering the effectiveness of the lecture and discussion methods in enhancing the adolescents’ knowledge and attitude towards premarital sexual behavior.A quasi experimental design, as well as pre-test post test non equivalent control group was carried out in this study. Discussion and lecture methods were treated as the independent variable. While the adolescents’ knowledge and attitude towards premarital sexual behavior lecture were handled as the dependent variable.There were two statistical tests used to analyze the data; Wilcoxon and Mann Whitney tests. Wilcoxon statistical test was utilized to test the difference of the adolescents knowledge and attitude before and after the treatments. Meanwhile, Mann Whitney statistical test was used to discover the effectiveness between the two methods.The study revealed two findings. First, the Wilcoxon statistical test showed that the lecture method resulted in students’ knowledge ( p=0,0001), and attitude (p=0,0001), while the discussion method resulted in students’ knowledge ( p=0,0001), and attitude (p=0,0007), Therefore, there was differentiation between students’ knowledge and attitude before and after the treatments. Second, the Mann Whitney statistical test proved that there was no difference between in effectiveness between lecture and discussion methods in enhancing students’ knowledge (p=0,636) and students’ attitude (p=0,102) towards premarital sexual behavior.Based on the findings, the students should be provided more counseling and information about adolescents reproductive health. The counseling can be carried out by combining lecture and discussion methods.Key words: premarital sexual behavior, group discussion, lecture, knowledge, attitude